PERLINDUNGAN HUKUM ASISTEN RUMAH TANGGA : STUDI KETERBATASAN DALAM UNDANG-UNDANG KETENAGAKERJAAN - Khalida, Diyah; Fatriani, Fennny (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
Household Assistants (ART) are a group of workers who have an important role in household life in Indonesia. The Labor Law in Indonesia, which should be a legal umbrella for all workers, does not fully provide adequate protection for domestic assistants. The unclear legal status of ART in Indonesia shows the urgent need for reform in labor regulations. With the ratification of the PPRT Bill and harmonization of national policies, it is hoped that the rights of household members can be more recognized and protected fairly throughout Indonesia. This article aims to weaken restrictions on the protection of domestic helpers in employment law. This type of research is normative legal research, which is carried out by analyzing statutory regulations relevant to certain legal issues.